Algoritms for Semantic Text Analysis for Security Threats - Liang, Jiqing (Харківський національний автомобільно-дорожній університет, 2024)
The purpose of this paper is to study the basic principles of SDN architecture and OpenFlow protocol, identify vulnerabilities, and build a threat model. Traditional hierarchical networks are no longer able to meet the needs of the modern world of big data, mobile and IoT devices, and cloud technologies. SDN architecture has been developed to address the problems of network flexibility and adaptability. The paper discusses the principles of SDN architecture, mechanisms of the OpenFlow protocol, describes their vulnerabilities, and provides recommendations for countering attacks. Also, an example of an application for automatic counteraction to DoS attacks is given.
Keywords: OpenFlow; SDN architecture; protocol; hierarchical networks; DoS attacks; IoT; BigData